Seven root canals in a deciduous maxillary molar detected by the dental operating microscope and micro‐computed tomography. Issue 6 (11th January 2016) - Ahmed, Hany Mohamed Aly; Khamis, Mohd Fadhli; Gutmann, James Leo
Summary: The root and root canal morphology of deciduous molars shows considerable variations. Consequently, a comprehensive understanding of the normal and unusual root and root canal configuration types in deciduous teeth is of prime importance. The purpose of this report is to describe a rare anatomical variation in a double‐rooted maxillary deciduous molar examined by the dental operating microscope and micro‐computed tomography. SCANNING 38:554–557, 2016. © 2016 Wiley Periodicals, Inc.